2017
DOI: 10.2514/1.c034087
|View full text |Cite
|
Sign up to set email alerts
|

Design Guidelines in Nonconventional Composite Laminate Optimization

Abstract: A method for optimising ply drop locations in composite laminates is developed using ideas from topology optimisation. The design is parametrised using a fibre angle and fictitious density distribution for each ply. The solution proceeds using a successive conservative convex approximations strategy. The structural responses are approximated separately in terms of the angle and fictitious density distributions of each ply. Explicit penalisation of intermediate densities is used to force the densities to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…They demonstrated that substantial structural improvements in strength, stiffness and buckling load could be reached by applying curved fibers. Other researchers have also contributed to the knowledge of flat tow-steered laminate plates [7][8][9][10][11]. Recent progress in variable-stiffness design and optimization of fiber-reinforced composite structures was summarized by Ghiasi et.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that substantial structural improvements in strength, stiffness and buckling load could be reached by applying curved fibers. Other researchers have also contributed to the knowledge of flat tow-steered laminate plates [7][8][9][10][11]. Recent progress in variable-stiffness design and optimization of fiber-reinforced composite structures was summarized by Ghiasi et.…”
Section: Introductionmentioning
confidence: 99%
“…This causes variable fiber angle and properties including the lamination stiffness compared with that of the CS composite structure. Thus, the variable fiber angle composite structure is usually called as the variable stiffness (VS) composite structure [9][10][11][12]. Figure 1 shows the layups for two different composite laminates.…”
Section: Introductionmentioning
confidence: 99%